تطبيق تعليم النحو بكتاب مختصر جدا لترقية إتقان القواعد النحوية لدى الطلاب - Muhammad Imamurrosyid; Isniyatun Niswah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
This book is an explanation of the book al-ajurumiyah. It contains the contents of the basic rules that make it easier for new students to understand them. The purpose of learning nahwu using the Mukhtashar Jiddan book is to enable students to easily understand nahwu rules and to accustom students to reading the yellow book which is studied by the majority of Islamic boarding schools. This research aims to identify the problems experienced by students who are also learning at university and their solutions. The qualitative descriptive research method is used. The required data will be obtained by means of observation, interviews and documentation techniques. The results of this research showed that some students face problems with learning grammar. The problems it encounters are the form of purely Arabic learning books, students' different abilities, lack of motivation, and the amount of time students use in university activities. The solution used to overcome these problems is to buy or borrow translated books to help students understand their education, and to hold graded classes, and teachers often motivate students to be enthusiastic about learning and memorization, and ask students to increase their time for learning and reduce university activities that are not very important